2012
DOI: 10.1103/physrevd.86.105037
|View full text |Cite
|
Sign up to set email alerts
|

Holographic fermions in charged Lifshitz theory

Abstract: We investigate the properties of holographic fermions in charged Lifshitz black holes at finite temperature through the AdS/CFT correspondence. In the charged Lifshitz background with the dynamical exponent $z=2$, we find that the dispersion relation is linear. The scaling behavior of the imaginal part of the Green function relative to $k_{\perp}=k-k_F$ is also discussed. We find, although the system has linear dispersion relation and quadratic quasi-particle width, it does not satisfy Luttinger's theorem. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
0
30
1
Order By: Relevance
“…Our results show that, different from the effect of dynamical exponent which suppresses the peak of the fermionic spectral function [36,45], the Lorentz-violation of fermions will enhance the peak and make the fermi momentum larger to compensate the non-relativistic bulk effect. Also, for fixed z, small Lorentz-violation of fermions corresponds the low energy excitation as non-Fermi liquid with nonlinear dispersion relation, when the Lorentz-violation becomes larger than a critical value, the low energy excitation always behaves as Fermi liquid with linear dispersion relation.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our results show that, different from the effect of dynamical exponent which suppresses the peak of the fermionic spectral function [36,45], the Lorentz-violation of fermions will enhance the peak and make the fermi momentum larger to compensate the non-relativistic bulk effect. Also, for fixed z, small Lorentz-violation of fermions corresponds the low energy excitation as non-Fermi liquid with nonlinear dispersion relation, when the Lorentz-violation becomes larger than a critical value, the low energy excitation always behaves as Fermi liquid with linear dispersion relation.…”
Section: Introductioncontrasting
confidence: 56%
“…However, the previous works usually started by adding relativistic fermions into the (non-)relativistic bulk theory. Since 1 The generalization of holographic fermions obtain many remarkable progress, such as the effects of different bulk theory on the fermionic correlation [31][32][33][34][35][36][37][38][39][40], holographic non-relativistic fermionic fixed points by imposing the Lorentz violating boundary condition [41][42][43][44][45], phase transition from the Fermi liquid to non-Fermi liquid and also to the Mott insulating phase due to the interaction between Dirac field and gauge field [46][47][48][49][50][51] and the fermionic spectral function effected by lattice effects [52][53][54][55][56], etc.. the anisotropic scaling (1) is built by construction in the HL gravity, it is natural to expect the coupling matters exhibit the same scaling in the same footing. This is the other motivation to introduce the probed non-relativistic fermions into the non-relativistic HL gravity and study the effect of the Lorentz-violation on the Fermionic spectral function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they find that this scaling behavior is controlled by conformal dimensions in the IR CFT dual to AdS 2 [4]. Subsequently, a lot of extensive explorations on the Fermi surface structure and associated excitations have also been implemented in more general geometries in [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and references therein. These holographic fermionic systems are expected to be candidates for generalized non-Fermi liquids and offer a possible clue to uncover the basic principle hidden behind the strangle metal phase.…”
Section: Introductionmentioning
confidence: 99%
“…It was showed that the Lifshitz exponent z in the holographic fermion systems plays an important role in the retarded Green's function [23,24]. For a specific value of the critical exponent z, the Luttinger's theorem is violated [25] and even a dynamical gap can be generated in the presence of a dipole coupling [26][27][28].…”
Section: Jhep11(2014)086mentioning
confidence: 99%